Studies towards a phosphorus(V)-catalysed Mitsunobu reaction - Shannon-Little, Andrew Laurence (2016)
A novel manifold has been developed, catalytic in phosphorus (V), that promotes the dehydration reaction of an alcohol to give the symmetrical ether product. This has been achieved through the development of a novel dioxyphosphorane catalyst that, in conjunction with a triflic acid cocatalyst, conducts the coupling reaction without the need for any additional stoichiometric reagents. This has allowed the omission of the explosive diazo-compounds that are required in the widely-accepted Mitsunobu conditions, and has reduced the amount of inconvenient and difficult-to-remove phosphorus waste that is usually associated with phosphorus-mediated reactions. This work constitutes the first example of a phosphorus (V)-catalysed Mitsunobu-type etherification reaction.